DIGITALIZATION OF MATHEMATICS LEARNING BASED ON PROBLEM SOLVING (International Conference on Social and Islamic Studies, 2022)
The Covid-19 pandemic requires learning activities to be carried out remotely so that it requires teachers to be skilled in presenting interesting learning to support a good learning environment. The use of digital technology can be an alternative to learning mathematics, not only as a medium for presenting material but also as a way to improve students' ability to solve problems. This study aims to explain the use of digital technology including its advantages and disadvantages, especially when viewed from the perspective of solving mathematical problems. The research method used is the method of literature review or literature study (library research). The literature taken is articles that have been published in various journals indexed by Scopus and Sinta (minimum Sinta 2). The analysis technique in this research is content analysis technique. Based on the literature that has been analyzed, it can be concluded that the use of digital technology in learning mathematics can improve students' skills in solving problems. Digital technology can assist students in illustrating problems, understanding problems, and solving them. For this reason, teachers need to train students' skills in operating various digital applications because they affect their ability to solve problems. The variety of technologies that can be used in learning allows teachers to choose suitable technology and can combine several applications to produce more optimal media.